2022
DOI: 10.5056/jnm21020
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Changes in Esophageal Body Movement During Bolus Transport After Peroral Endoscopic Myotomy in Type III Achalasia

Abstract: Background/AimsThe effect of peroral endoscopic myotomy (POEM) on esophageal body movement in achalasia is poorly understood. This study aims to evaluate morphological changes in esophageal body movement after POEM in type III achalasia by analyzing intraluminal ultrasound (US) images in comparison to type I and II achalasia. MethodsIntraluminal US images and impedance values of the distal esophagus from 47 achalasia patients who underwent POEM or pneumatic dilatation (PD) (30 patients in the POEM group and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Because achalasia generates the opposite symptom of reflux by acting as a natural barrier, cardiomyotomy could imply acid exposure to a more sensitive esophageal mucosa, which was already affected by food stasis fermentation, with microscopic changes mimicking reflux and lymphocytic esophagitis [ 50 ]. A hypothesis to this waning between-group difference over time might be attributed to a late esophageal remodeling, which involves the improvement of the esophageal wall tortuosity, the lumen diameter reduction [ 51 ], and improvement in the clearance of food stasis, which prevents fermentation and decreases GERD in the endoscopic group. Another explanation could be the wrap loosening in the HMF group over time, which may lead to intrathoracic migration or hiatal hernia recurrence, partial or complete wrap disruption, and fundoplication failure [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…Because achalasia generates the opposite symptom of reflux by acting as a natural barrier, cardiomyotomy could imply acid exposure to a more sensitive esophageal mucosa, which was already affected by food stasis fermentation, with microscopic changes mimicking reflux and lymphocytic esophagitis [ 50 ]. A hypothesis to this waning between-group difference over time might be attributed to a late esophageal remodeling, which involves the improvement of the esophageal wall tortuosity, the lumen diameter reduction [ 51 ], and improvement in the clearance of food stasis, which prevents fermentation and decreases GERD in the endoscopic group. Another explanation could be the wrap loosening in the HMF group over time, which may lead to intrathoracic migration or hiatal hernia recurrence, partial or complete wrap disruption, and fundoplication failure [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…In conclusion, many other reports aimed to compare the outcomes of different treatments such as laparoscopic Heller myotomy, POEM, and PD, 2 , 3 and found limitations due to “heterogeneity” among the studies. Differently, Kim et al 1 by pathophysiological methods, reveals that the morphological structure alteration is explainable to functional impairment from the different subtypes of achalasia, therefore efficacy of POEM and PD is different across to the different subtype of achalasia. In other words, given that the different subtype of achalasia exists with the different etiology and pathophysiology, then, it is not logical for 1 therapeutic procedure to treat all different achalasia situations.…”
mentioning
confidence: 96%
“…TO THE EDITOR: The article entitled “Morphologic changes in esophageal body movement during bolus transport after peroral endoscopic myotomy in type III achalasia” authored by Kim et al 1 published in your esteemed journal has been reviewed and discussed with great interest. This study presents that the different subtype of achalasia has different morphological abnormality in muscle contour at esophageal body that could be as one of the rationales when considering whether peroral endoscopic myotomy (POEM) or pneumatic dilatation (PD) could be a better way to the specific subtype of achalasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Authors obtained a good efficacy of POEM in consistent to other studies. 2 , 3 However, all of those cannot be for prediction in correlative to POEM efficacy. Thus, Hsing et al 1 suggested that the POC is one of critical indexes reflecting a good restoration of motility function of lower esophagus sphincter, which was seen in 8%, 67%, and 25% respectively from type-I, -II, and -III achalasia after POEM, ie, there is a better expectation from POEM in achalasia subtype II than I or III.…”
mentioning
confidence: 99%